Ecological risk assessment of mixtures of radiological and chemical stressors: Methodology to implement an msPAF approach. (December 2017) - Beaumelle, Léa; Della Vedova, Claire; Beaugelin-Seiller, Karine; Garnier-Laplace, Jacqueline; Gilbin, Rodolphe
Abstract: A main challenge in ecological risk assessment is to account for the impact of multiple stressors. Nuclear facilities can release both radiological and chemical stressors in the environment. This study is the first to apply species sensitivity distribution (SSD) combined with mixture models (concentration addition (CA) and independent action (IA)) to derive an integrated proxy of the ecological impact of combined radiological and chemical stressors: msPAF (multisubstance potentially affected fraction of species). The approach was tested on the routine liquid effluents from nuclear power plants that contain both radioactive and stable chemicals. The SSD of ionising radiation was significantly flatter than the SSD of 8 stable chemicals (namely Cr, Cu, Ni, Pb, Zn, B, chlorides and sulphates). This difference in shape had strong implications for the selection of the appropriate mixture model: contrarily to the general expectations the IA model gave more conservative (higher msPAF) results than the CA model. The msPAF approach was further used to rank the relative potential impact of radiological versus chemical stressors. Graphical abstract: Highlights: msPAF methodology was applied on mixtures of radiological and chemical stressors. A consistent set of chronic SSDs was collected for ionising radiation and 8 stable chemicals. The SSD of ionising radiation had lower steepness than the SSD of stable chemicals. This resulted in higher msPAF values based on the IA than on the CA mixture model. Abstract : The msPAF approach combining SSD and mixture models was used for the first time on mixtures of radiological and chemical stressors.